ReFocus: The Films of Lucrecia Martel - Punte, Maria Jose (Imagofagia, 2023)
Sobre Natalia Christofoletti Barrenha, Julia Kratje y Paul R. Merchant (eds.). ReFocus: The Films of Lucrecia Martel. Edinburgh: Edinburgh University Press, 2022, 211 pp., ISBN 978 4744 8524 1 (webready PDF).